The Effects of 401(K) Participation on the Wealth Distribution: An Instrumental Quantile Regression Analysis - Chernozhukov, Victor; Hansen, Christian (The Review of Economics and Statistics, 2004)
We use instrumental quantile regression approach to examine the effects of 401(k) plans on wealth using data from the Survey of Income and Program Participation. Using 401(k) eligibility as an instrument for 401(k) participation, we estimate the quantile treatment effects of participation in a 401(k) plan on several measures of wealth. The results show the effects of 401(k) participation on net financial assets are positive and significant over the entire range of the asset distribution, and that the increase in the low tail of the assets distribution appears to translate completely into an increase in wealth. However, there is significant evidence of substitution from other forms of wealth in the upper tail of the distribution.